(untitled) (Medico Legal Update, 2021)
Background: IHD has been regarded as a universal burden. Even though women are sheltered from this dreadful disease during their reproductive years to a certain extent, the incident is almost similar in both genres after menopause. Since women are regarded as the centre of domestic chores in our home settings, any bodily ailments affecting her directly impact thesynchrony of a family. Aim: This study aimed to describe lived experience of women with IHD to offer a deeper understanding in caregivers, which will help them while taking care of patients and further it will act as a guide to nursing practice. Objective: To explore the lived experiences of women with IHD Settings and Design: Setting of the study was Malabar Medical College Hospital and Research Centre. Qualitative study, in which descriptive phenomenological design was used for the study. Materials and Method: The sample of the study included 10 women with Ischemic heart disease who underwent CABG or PTCA from Malabar Medical College Hospital and research centre, Calicut. In depth interviews were conducted within one month to one year of their disease condition. Interviews were recorded and audio files were transcribed. Colaizzi’s method was used to direct data analysis and the structure of the phenomenon was formulated. Statistical Analysis used: N Vivo software version (9) was used for the study. Results: Significant statements were extracted from the transcribed verbatim and meanings were formulated. Total of seven main themes and several subthemes were emerged; the themes were 1. Pain perception. 2. Fear of impending death. 3. Anxiety 4. Stumbling blocks. 5. Support system. 6. Breakdown the barriers. Conclusion: The study reflected the pain and sufferings underwent by the patients during the disease process and the factors that helped them for the recovery and their insights to live along with this dreadful disease in their later life.